Da ancestralidade, da oralidade e da performance presentes no coco de roda e na ciranda de Odete de Pilar: um caminho para o estudo da literatura brasileira no ensino fundamental - Monte , Joan Saulo Ramos do (2023)
Popular culture, as a set of instituted knowledge and the result of interaction between individuals, configures a cluster of elements that act in the composition of society. The coco de roda and the ciranda are cultural manifestations that allow the active participation of the players, whether singing or dancing. It is in this context that Odete de Pilar, as a teacher of popular culture, stands out, as she owns a voice that promotes the appreciation of coconut and ciranda in Paraíba, as she contributes to the maintenance of cultural heritage, as well as popular traditions. and ancestral voices with a view to performances as a means of promoting common unity. Since 1992, Odete's cocos and cirandas have enchanted the people who listen to them. Living in the rural area of Pilar-PB, Odete began to stand out in the artistic and cultural scene of Paraíba from 1992 onwards, after the records and memories of popular culture made by Ignez Ayala and Marcos Ayala (1992 - 2000). Owner of an unmistakable voice, Odete has influenced several artists with her compositions. From that, the need arose to study Odete's woman-voice as a diffuser of her art. Thus, we see the need to carry out an analysis about the influence of coco de roda and ciranda for the development of skills regarding the teaching of Brazilian literature in the classroom, allowing the contact of students with popular literature in compliance with what prescribes the Law 10.639/03 and the National Day of Traditions of Roots of African Matrices and Nations of Candomblé. The research had as participants the students of the 7th year of Elementary School of the Maria Alves de Brito State School, in the city of Pilar-PB, and it was endowed with a qualitative approach of interventionist nature that propitiated the work with the coco de roda and the ciranda. in the classroom as a cultural manifestation through the use of didactic sequences and pedagogical workshops. In addition, as a methodological basis used in the work, we used ethnographic research covering the years 2019 to 2023, using participant observation, audiovisual recordings and informal interviews. To base our research, we take into account the contributions of Andrade (1984), Ayala (2015), Bortoni-Ricardo (2008), Paviani & Fontana (2009), Zumthor (1993 - 2008), Fanon (2008), Hall (1997 -2006), among others. The results obtained showed that the ciranda and the coco de roda, in the context of literature and popular culture, constitute performative elements that, through the body and voice, are endowed with the competence of materializing perception and awakening the belonging and appreciation of cultures of oral traditions. , thus contributing as tools for revealing ancestry and facilitating the promotion of collaborative social interactions aided by music, dance, space-time, dasein and performance, thus constituting important artistic-literary products regarding the teaching of literature and breaking with the coloniality of knowledge and power, as they contribute to distancing from universalized Eurocentric thinking to give way to voices and knowledge that have been made inferior, distorted and erased by history.